Regimes próprios de previdência social, trajetória recente e perspectivas: análise a partir do caso do estado de Minas Gerais - Duarte, Jean Mattos (2017)
This dissertation carried out a study about the public pension system foreseen in the Brazilian legal system and applicable to the public servants of the federation entities, focusing on the recent trajectory of the State of Minas Gerais case study, with the purpose of evidencing the organization of the system and to understand the relationship between social security and social security expenditures with Minas Gerais fiscal scenario from 2002 to 2015, and thus to identify challenges and possibilities, since, despite significant reforms started in the 1990s, there are still problems to be addressed nationally. The research considered the retrieval of literature on the subject, administrative documents and data provided by the Minas Gerais State Secretariat for Planning and Management, as well as by the Institute of Pension of the State of Minas Gerais. To achieve the objectives, a general characterization of social security was carried out with the elucidation of origins and concepts relevant to understanding the theme. Demographic variables such as life expectancy and fertility rate, which are closely related to the impacts on social security financing, are presented and permeate the debates related to the respective reforms. From this point of view, it focuses on the specific case of social security in Brazil, with a historical redemption demarcated by the periods before and after the Federal Constitution of 1988, in which it was possible to verify the differentiated historical treatment conferred on public servants to the detriment of other workers with respect to social security benefits and its financing model essentially supported by public resources. It´s made a rescue of the reforms carried out in order to corroborate the need for constant search for adaptation of social security rules to the demographic parameters and with sustainable financing models, but without losing sight of the need to adopt mechanisms that enable a life with dignity for those who do not have more work capacity. Finally, it´s analyzed the social security expenditures in the context of the public budget, with a focus on the fiscal scenario of the State of Minas Gerais, in order to highlight the issues discussed and the need for adjustments, especially in the context of fiscal crisis experienced from a certain point of the analyzed period, allowing to indicate that measures are still necessary regarding the fiscal management of personnel expenses and also of adjustments in the social security rules applicable to the public sector.